2013
DOI: 10.1002/cncr.28090
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture: Could an ancient therapy be the latest advance in the treatment of lymphedema?

Abstract: The BackgroundOne of the most common complications of breast cancer treatment is lymphedema, an incurable condition that affects the lives of approximately 800,000 US breast cancer survivors.1,2 If not detected early and treated, clinical signs and symptoms can develop from the accumulation of lymphatic fluid in the tissues of the affected arm and remaining breast quadrant. Although established therapies for lymphedema management exist, there remains a need for other modalities that can further improve outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Over the past decade, there has been a dramatic increase in the use of complementary and alternative medicines by cancer patients despite limited research available to support their use [6]. In this regard, acupuncture has been used to treat the side effects of cancer therapy as well as the fatigue, pain, sleep disturbances, and lymphedema associated with many types of tumors [13, 32, 33]. While there are a number of studies that have provided evidence for the antinociceptive, antifatigue, and antiemetic effects of EA in cancer patients [4, 33], there is only one case report that suggests that acupuncture may actually affect the tumor itself (by causing regression of human ductal carcinoma [34]).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been a dramatic increase in the use of complementary and alternative medicines by cancer patients despite limited research available to support their use [6]. In this regard, acupuncture has been used to treat the side effects of cancer therapy as well as the fatigue, pain, sleep disturbances, and lymphedema associated with many types of tumors [13, 32, 33]. While there are a number of studies that have provided evidence for the antinociceptive, antifatigue, and antiemetic effects of EA in cancer patients [4, 33], there is only one case report that suggests that acupuncture may actually affect the tumor itself (by causing regression of human ductal carcinoma [34]).…”
Section: Discussionmentioning
confidence: 99%
“…While the physiological mechanisms behind the analgesic effects of acupuncture are unclear, it is believed that it proceeds by release of endogenous opiates and neurotransmitters at the systemic and local tissue levels 12 . It has been suggested that the effect of acupuncture are mediated through electrical stimulation of the central nervous system (CNS) 13 , leading to reduced tissue inflammation and fibrosis via increased influx of anti-inflammatory cytokines and efflux of toxins, cellular debris, and proteins 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphedema is a potential adverse effect caused by surgery or radiotherapy injury, which is defined as soft tissues swelling as a result of accumulation of protein-rich interstitial fluid [34,35]. Breast cancer-related lymphedema (BCRL) is a chronic disease that can lead to edema, hypertrophy, and even fibrosis of the upper extremity.…”
Section: Possible Rationale Of Amt For Bcrlmentioning
confidence: 99%